Comparison of Changing Population Exposure to Droughts in River Basins of the Tarim and the Indus - Anqian Wang; Yanjun Wang; Buda Su; Zbigniew W. Kundzewicz; Hui Tao; Shanshan Wen; Jiancheng Qin; Yu Gong; Tong Jiang (Earth's Future, 2020)
Abstract Droughts are major, large‐scale, weather‐driven natural disasters, on the rise in the changing climate. We project changing population exposure to drought in two vulnerable, adjacent, basins of large rivers, the Tarim River Basin (TRB) and the Indus River Basin (IRB), for the future horizon 2021–2065. Drought events are assessed based on the outputs of multiple Global Climate Models, by applying the Standardized Precipitation Evapotranspiration Index (SPEI) and the Intensity‐Area‐Duration method (IAD). Future population exposure to droughts is evaluated by combining the drought events under three RCP scenarios (RCP2.6, RCP4.5, and RCP8.5) with the projected population from Shared Socioeconomic Pathways (SSPs), acknowledging the recent two‐child policy in China. Results show that frequency of drought events in both river basins could increase in the future, while increase in the TRB is stronger than in the IRB. The areal coverage of drought events in both river basins is projected to be greater in 2021–2065 than in 1961–2005. Increase of frequency and areal coverage in both basins is especially strong for the class of extreme drought events. According to the ensemble mean of multi‐GCMs, population exposure to droughts was 25.0% and 20.9% of the total population in the TRB and the IRB, respectively, in 1961–2005, and it is projected to increase by over 60% for the TRB and to increase by over 30% for the IRB, in 2021–2065.